Analisis Pengaruh Sosial Media Marketing, Guerilla Marketing, Ulasan Influencer & E-Service Quality Terhadap Keputusan Pembelian Sepatu Ventela (Studi Kasus Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Mahfud, Ah Syaifudi; Rizal, Mohammad; Rahman, Fahrurrozi (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This study aims to analyze the impact of social media marketing, guerrilla marketing, influencer reviews, and e-service quality on the purchasing decisions of Ventela shoes at the Faculty of Economics and Business, Universitas Islam Malang. This research employs a quantitative approach with an explanatory research method. The population of the study consists of Ventela shoe users at the faculty, with a sample determined using Malhotra's formula, totaling 135 participants through purposive sampling. Primary data was collected by distributing questionnaires to students who met the criteria, namely those who have purchased Ventela shoes. The results of the coefficient of determination test show that the Adjusted R Square is 51.6%, which means that the variables of social media marketing (X1), guerrilla marketing (X2), influencer reviews (X3), and e-service quality (X4) explain 51.6% of the variability in purchasing decisions, while the remaining 48.4% is explained by other factors outside the research model.The conclusions of this study are as follows: (1) Social media marketing, guerrilla marketing, influencer reviews, and e-service quality simultaneously have a significant impact on the purchasing decisions of Ventela shoes; (2) Social media marketing, guerrilla marketing, influencer reviews, and e-service quality each have a significant effect on the purchasing decisions of Ventela shoes. These findings provide valuable insights for marketing strategies and product development in the footwear market. Keywords: Social Media Marketing, Guerrilla Marketing, Influencer Reviews & e-Service Quality and Purchasing Decisions